2009
DOI: 10.1007/s00267-009-9356-y
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Aquaculture Development in Bangladesh: Unsustainable and Sustainable Experiences

Abstract: Coastal aquaculture in Bangladesh consists mainly of two shrimp species (Penaeus monodon and Macrobrachium rosenbergii). Currently, there are about 16,237 marine shrimp (P. monodon) farms covering 148,093 ha and 36,109 fresh water shrimp (M. rosenbergii) farms covering 17,638 ha coastal area. More than 0.7 million people are employed in the farmed shrimp sector and in 2005-2006 the export value of shrimp was 403.5 million USD. Thus, coastal aquaculture contributes significantly to rural employment and economy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 31 publications
0
74
0
2
Order By: Relevance
“…The shrimp culture in Ecuador has transformed the regional balance of the economy with respect to production, employment and habitation [40]. Similarly, the economic benefits of shrimp aquaculture in Asia are well recognized including employment opportunities [36,41,42]. Additionally, this industry contributes to poverty reduction and food security, as well as generates employment from seed collectors to exporters [43].…”
Section: Development and Characteristics Of Shrimp Farmingmentioning
confidence: 99%
“…The shrimp culture in Ecuador has transformed the regional balance of the economy with respect to production, employment and habitation [40]. Similarly, the economic benefits of shrimp aquaculture in Asia are well recognized including employment opportunities [36,41,42]. Additionally, this industry contributes to poverty reduction and food security, as well as generates employment from seed collectors to exporters [43].…”
Section: Development and Characteristics Of Shrimp Farmingmentioning
confidence: 99%
“…These two factors together provided a catalyst to accelerate shrimp farming (Karim, 1986). From 1979 to 1980, slightly more than 20 000 ha were placed under shrimp production (Ahmed, 1988), an area that had increased to c. 240 000 ha by the 2008-2009period (DoF, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…In the wet season, Azad et al (2009) found that about 75% of farmers in the south-western zone and 98% in the central zone cultured fresh-water shrimp in their low-lying land. Furthermore, about 68% of farmers in the south-west and 75% in the central zone grew wet-season rice and fresh-water shrimp together in the gher in this season.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Shrimp farming has made a considerable contribution to the economy of the country in terms of foreign exchange earnings, as well as to the livelihoods of farm families by increasing their income, generating employment, and increasing food availability (Azad et al 2009;. In 2001-02, about 0.6 million people were employed in the shrimp sector (Islam et al 2005).…”
Section: Yearmentioning
confidence: 99%
See 1 more Smart Citation